#Survivinghighschool : do it for the vine : a novel - Pons, Lele , 1996-; De la Cruz, Melissa , 1971- (Gallery Books, 2016)
"Lele is a bulls-eye target at her new school in Miami until, overnight, her digital fame catapults the girl with cheerleader looks, a seriously silly personality, and a self-deprecating funny bone into the popular crowd. Now she's facing a whole new set of challenges--the relentless drama, the ruthless cliques, the unexpected internet celebrity--all while trying to keep her grades up and make her parents proud"